Separate waste collection as key to effective implementation of the «garbage» reform - Yu. V. Plokhikh (Омский научный вестник: Серия "Общество. История. Современность")
The article considers the current problem for our country-separate collection of waste, the main source of which is the housing stock. It is shown that the absence of marked containers near residential buildings does not allow sorting garbage «at the source», which hinders the further rational use of resources. The author offers a classification of garbage collection methods used in the regions of our country, and highlights the most accessible of them. The article indicates that due to the lack of capacity and funds, small businesses can only be involved in certain stages of waste management that do not require expensive investments